2006
DOI: 10.1016/j.ejvs.2006.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Disease Treated by Ultrasound Guided Foam Sclerotherapy

Abstract: This technique is useful in the management of chronic venous disease as an alternative to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 24 publications
3
101
1
3
Order By: Relevance
“…They also suggested longer initial compression, lasting for more than 2 weeks. 12 The site of insertion of the intravenous cannula, volume of foam and its production and the concentration of the sclerosant used were in accordance with the Consensus from the 2 nd meeting on foam sclerotherapy. Follow-up examinations were done to assess the efficacy of the treatment and for appropriate management in case of any complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested longer initial compression, lasting for more than 2 weeks. 12 The site of insertion of the intravenous cannula, volume of foam and its production and the concentration of the sclerosant used were in accordance with the Consensus from the 2 nd meeting on foam sclerotherapy. Follow-up examinations were done to assess the efficacy of the treatment and for appropriate management in case of any complications.…”
Section: Discussionmentioning
confidence: 99%
“…Similar follow-up has also been suggested by several other authors. [12][13][14][15] An ultrasound examination was done a week after therapy showed optimum obliteration of the treated vein in all the cases and also showed no signs of DVT. Thus re-sclerotherapy was not required.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat higher than reported in other studies. In Coleridge study [15] the reported complications were as follow, thrombophlebitis occurred in a small number of patients (5%) and was managed by analgesia, compression and aspiration of thrombus. Calf vein thrombosis was confined to isolated gastrocnemius veins or to part of the posterior tibial vein (1.23%) All resolved with compression by stocking or bandage and exercise without use of anticoagulants.…”
Section: Citationmentioning
confidence: 99%
“…In Coleridge study [15], 459 limbs have been reviewed at 6 months or more following treatment, average 11 months and range 6-46 months. This includes 363 of 886 GSVs and 141 of 263 SSVs.…”
Section: Citationmentioning
confidence: 99%
“…Techniques for ablation of superficial veins and malformations are individualized and may include sclerotherapy with alcohol or foam, that showed a good success but can cause nerve injury and cutaneous damage [47]. Foam sclerotherapy, with sodium tetra decyl sulphate and polidocanol, has been shown to be of a low risk and effective treatment for superficial venous disease [48,49]. Patient's cosmetic satisfaction with multiple session foam sclerotherapy has been reported in about 71.5% of treated patients [50].…”
Section: Managementmentioning
confidence: 99%